Clinical Simulation in Cardiology Teaching: Systematic Review - Muñoz Gualán, Germán Geovanny (2024)
Clinical simulation seeks to guarantee the development of clinical skills, oriented towards correct quality of care and patient safety. Objective: Identify the efficiency of clinical simulation in cardiology teaching. Method: A bibliographic review was carried out using the PRISMA protocol. The information was collected in the first half of 2023, using the search engines in PubMed, Scopus and Web of Science, by title, considering the documents from 2019 to 2024, which show some association between the MeSH terms used, which included: “simulation training”, “education” and “cardiology”. Development: In the identification, after the search carried out, 2117 articles were located, in the screening there were 117 articles, in the evaluation for eligibility with 70 articles, to finally include 19 useful articles for this review. Conclusions: Clinical simulation in the teaching of cardiology is pedagogically supported by a university training model, where significant learning is stimulated to achieve the competencies established in the curricula of the medical career study plans.